Analisis Sentimen Mengenai Childfree Menggunakan Metode Naïve Bayes: Analisis Sentimen Mengenai Childfree Menggunakan Metode Naïve Bayes - Yeni Safitri; Rakhmat Kurniawan; Suhardi (AI Society & STMIK Indonesia, 2024)
The emergence of the issue of childfree has become a trending topic on Twitter since the beginning of 2020 until now, which has given rise to many positive and negative opinions from various groups, especially on Twitter social media. This sentiment analysis research aims to determine the responses given regarding childfree in the form of positive, neutral or negative opinions by collecting Twitter data. The number of datasets used is 700 data, divided into 630 training data and 70 test data. This research uses the Naïve Bayes algorithm classification and confusion matrix as a performance evaluation of the system being built. The test results show an accuracy value of 64.29%, precision of 68.25%, recall of 64.29% and fi-score of 55.69%.